Clays and Clay Minerals, Vol. 57, No. 5, 566–577, 2009. - Papoulis, Dimitrios; Tsolis-Katagas, Panagiota; Kalampounias, Angelos G.; Tsikouras, Basilios (My University, 2009)
Occurrences of halloysite-rich material in altered volcanic rocks, principally trachyandesites, dacites, and tuffs, extend over an area of ~1 km2 in the southwestern part of Limnos, Island, northeast Aegean Sea, Greece. The present study was designed to investigate the alteration processes which acted on the biotite in these volcanic rocks, to describe in detail the mechanism of formation of the halloysite, and to specify the mechanisms of formation of anatase during the alteration processes. Samples were examined using polarized-lightmicroscopy, X-ray powder diffraction, scanning electron microscopy, scanning electron microscopy-energy dispersive spectroscopy, and Fourier-transform-Raman techniques. The extensive alteration of the parent rocks, triggered by the circulation of hydrothermal fluids through faults and fractures, resulted in the alteration of biotite to halloysite. Six stages of alteration were recognized. Nanoparticles of halloysite were initially formed on the mica layers, which progressively grew through short-tubular to well formed tubular halloysite, with increasing alteration. In the most altered samples, laths and interconnected laths with the composition (Al3.96Fe0.04)Si4O10(OH)8, were the dominant halloysite morphologies. Anatase was encountered as an alteration product of both ilmenite and biotite. Ilmenite was altered to anatase and Fe oxides. The altered ilmenite crystals constrained most of the newly formed anatase within the space occupied previously by ilmenite, leading to the formation of skeletal anatase. The layered structure of the micas was the main factor governing the morphology of newly formed anatase developed outside ilmenite margins in the form of layers parallel to those of mica. An unusual ringlike structure of anatase was thought to be the result of the uncommon alteration of inner parts of mica folia to tubular halloysite oriented perpendicular to the mica layers. The detachment of the halloysite tubes by circulating hydrothermal fluids was considered to be the reason for the creation of holes which were subsequently surrounded by the anatase ring forms.
Progressive Formation Of Halloysite From The Hydrothermal Alteration Of Biotite And The Formation Mechanisms Of Anatase In Altered Volcanic Rocks From Limnos Island, Northeast Aegean Sea, Greece
gsccm57505-pap.pdf- 1.19MB
Keywords: Periodicals; Geology; Anatase; Biotite; Greece; Halloysite; Hydrothermal alteration; Limnos; SEM